Analisis Implementasi Kepemimpinan Transformasional Dalam Organisasi Mahasiswa - Harefa, Darmianus; Korengkeng, Yossy; Linda, Oktrin; Sahiundaleng, Karmila; Tangkere, Tesalonika; Lengkong, Febriela (Jurnal Manajemen Pendidikan Kristen, 2024)
Leadership is a crucial element in human life, particularly in a social context. Transformational leadership plays a significant role in shaping the performance of its members. This leadership style has been shown to enhance the spirit and enthusiasm of organizational members. The method used in this research is descriptive qualitativewith a case study approach, allowing the researcher to explore phenomena in depth and systematically. This study references previous research titled "An Overview of Transformational Leadership Stylesin Student Organizations" (Bantam et al., 2024). Theaim of this research is to analyze the implementation of transformational leadership within the context of student organizations, specifically in the Student Association of the Psychology Department (HIMAPRO) for the 2023-2024 academic year. This study reveals that the application of transformational leadership theory, as described by McShane and Von Glinow (2010), has a positive impact in the context of student organizations, particularly in HIMAPRO